Pengaruh Harga dan Kualitas Produk Terhadap Keputusan Pembelian pada Kentucky Fried Chicken (KFC) di Cabang Karawang Galuh Mas - Sefina Titi Aisa; Enjang Suherman; Laras Ratu Khalida (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of the study was to analyze purchasing decisions at Kentucky Fried Chicken (KFC) at the Karawang Galuh Mas branch which can be influenced by price and product quality. Using quantitative methods, through a focus on price and product quality variables. For sampling techniques, this study used purposive sampling, selecting samples based on specific criteria in accordance with research needs. Namely KFC consumers at the Karawang Galuh Mas branch. Data for this study were obtained through a questionnaire distributed to 96 respondents, then with a sample selection based on the Lemeshow formula. Data analysis was carried out through multiple regression to understand the relationship between variables thoroughly. While the classical assumption tests used in this study include normality test, multicollinearity test, and heteroscedasticity test with the help of the SPSS (Statistical Product and Service Solutions) version 27 program. The results of this study indicate that price and product quality have a positive and significant effect on purchasing decisions at Kentucky Fried Chicken (KFC) at the Karawang Galuh Mas branch.